PREDIKSI NILAI OBLIGASI PEMERINTAH DAN RETURN BANK-BANK REKAP - Indratmo Yudono (Faculty of Economics and Business Universitas Jenderal Soedirman, 2009)
The research of the treasury bonds case study is entiled “The Prediction Value of Treasury Bonds and Return of The Recapitalized Banks”. It was aimed at predicting about value of the interest bearing bonds to find out the predictor of the growth of interest rate and value of bonds lag ; predicting about value of variable interest bearing bonds to find out the predictor of profit and loss sharing ; selecting the best model from the models applied in this research ; finding out and analyzing return of the recapitalized bank. The tested hypotheses of the research were : 1) the growth of interest rate and the sluggish value of bonds met the conditions of model to predict value of bonds, 2) profit and loss sharing met the conditions of model to predict value of bonds, 3) profit and loss sharing based on model was better than that of the interest based one, and 4) the return of the recapitalized banks tended to increase. The first hypotesis was tested by linier regression model, the second hypotesis was tested by linier regression model and linier log regression model ; Mac Kinnon, White dan Davidson (MWD) test was applied and the result showed that the condition did not met, the second hypotesis was continued to test by Log-log Invers (LLI) model,The third hypotesis was tested by ten criteria selecting model namely AIC, FPE, GCV, HW, RICE, SCHWARZ, SQWASQ, SHIBATA, PC, RVC, and the fourth hypotesis was tested by linier trend model. The study concluded the followings : 1) the growth of the interest rate and the sluggish value of bonds met the conditions of model to predict value of variable rate bonds, 2) profit loss sharing met the conditions of model the predict calue of variable rate bonds, 3) profit loss sharing based on model was better than that of the interest based one, 4) the return of the recapitulazed banks tended to increase.